The Effect of Export, Import, and Exchange Rates of Economic Growth on China - Eni Setyowati; Kinanti Diva Karisma (Economic Reviews Journal, 2024)
This research analyzes the impact of exports, imports, exchange rates, and economic growth in China using data on export, import, and exchange rate activities during the period 1981-2020. The research conducted with a quantitative method, utilizing multiple regression analysis to examine the relationships between these variables. The findings indicate that exports, imports, and exchange rates significantly influence China's economic growth. The results suggest that exports and exchange rates have a positive and significant effect on economic growth in China, while imports have a positive but not significant impact on economic growth in China.